1999
DOI: 10.1016/s0006-3495(99)77018-9
|View full text |Cite
|
Sign up to set email alerts
|

The Actin-Based Nanomachine at the Leading Edge of Migrating Cells

Abstract: Two fundamental parameters of the highly dynamic, ultrathin lamellipodia of migrating fibroblasts have been determined-its thickness in living cells (176 +/- 14 nm), by standing-wave fluorescence microscopy, and its F-actin density (1580 +/- 613 microm of F-actin/microm(3)), via image-based photometry. In combination with data from previous studies, we have computed the density of growing actin filament ends at the lamellipodium margin (241 +/- 100/microm) and the maximum force (1.86 +/- 0.83 nN/microm) and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
188
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(221 citation statements)
references
References 57 publications
29
188
3
1
Order By: Relevance
“…Other experiments however (22,23) suggested that the propelling force is much larger, of the order of few nN. Likewise, the force exerted by the lamellipodium on a moving cell is of the order of a few nN (24). The discrepancies described above call for direct measurements of the force generated by actin polymerization, which are carried out here.…”
mentioning
confidence: 73%
“…Other experiments however (22,23) suggested that the propelling force is much larger, of the order of few nN. Likewise, the force exerted by the lamellipodium on a moving cell is of the order of a few nN (24). The discrepancies described above call for direct measurements of the force generated by actin polymerization, which are carried out here.…”
mentioning
confidence: 73%
“…Without additional chemical or mechanical cue, these cells are polarized, adherent and spontaneously motile. An active lamellipod, which extends in the cell front, is considered to act as the motor of the migration machinery via actin polymerization 10 . The central body is mainly occupied by the nucleus and at the cell rear, the uropod is a characteristic organelle of T lymphocytes whose role in cell migration remains enigmatic 11 .…”
Section: Resultsmentioning
confidence: 99%
“…2D), a 15% curvature bias corresponds to a radius of curvature of 2.3 ÎŒm and a bending energy of 0.6 k B T per ÎŒm of ATPbound filament (40). This amount of curvature could result from a lateral force of 1 pN applied perpendicularly to the end of a 0.05-ÎŒm-long filament fixed at the other end (44), which reflects the average force per filament due to membrane tension and rigidity (45,46) and the approximate length of free F-actin (47) at the leading edge of the cell. If the length of free F-actin is longer at the leading edge (48,49), the filaments require even less force to bend.…”
Section: A Fluctuation Gating Model For Branching By the Arp2/3 Complmentioning
confidence: 99%